2020
DOI: 10.15446/rcciquifa.v49n2.88854
|View full text |Cite
|
Sign up to set email alerts
|

Domestic wastewater treatment plants as sources of macrolide-lincosamide-streptogramin B- and penicillin-resistant Staphylococcus aureus in Brazil

Abstract: Staphylococcus aureus is one of the main bacteria that affect human health. Its reduced susceptibility to beta-lactam antibiotics has driven the clinical use of macrolides and lincosamides. However, the presence of macrolide-lincosamide-streptogramin B (MLSB)-resistant S. aureus strains is increasingly common. Wastewater treatment plants (WWTPs) are the main anthropogenic source of resistance determinants. However, few studies have assessed the importance of this environment on the dissemination of MLSB-resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…On the other hand, lincosamides are a highly important antibiotics class, used against infections caused by Enterococcus sp., and Staphylococcus aureus. Due to the reduced susceptibility of S. aureus to -lactam antibiotics, the clinical use of macrolides and lincosamides against penicillin-resistant S. aureus has been promoted [84]. Bruyndonckx et al, (2021) reported that lincosamides were among the most consumed classes in Sweden and accounted for more than 20% of macrolides, lincosamides and streptogramins consumption in Austria, Finland, Germany, Hungary, and Luxembourg between 1997 and 2017 [52].…”
Section: Chlortetracymentioning
confidence: 99%
“…On the other hand, lincosamides are a highly important antibiotics class, used against infections caused by Enterococcus sp., and Staphylococcus aureus. Due to the reduced susceptibility of S. aureus to -lactam antibiotics, the clinical use of macrolides and lincosamides against penicillin-resistant S. aureus has been promoted [84]. Bruyndonckx et al, (2021) reported that lincosamides were among the most consumed classes in Sweden and accounted for more than 20% of macrolides, lincosamides and streptogramins consumption in Austria, Finland, Germany, Hungary, and Luxembourg between 1997 and 2017 [52].…”
Section: Chlortetracymentioning
confidence: 99%
“…Among the species included in the genus, Staphylococcus aureus is the most clinically important, its incidence varies between 10 to 30 cases per 100 000 people per year, in which the most affected ages are at the extremes of life (children and the elderly), being the black population was shown to be prevalente [12,13].…”
Section: Introductionmentioning
confidence: 99%